Reduction of adaptation to high-energy diets using virginiamycin: effects on ruminal fermentation - Squizatti, M. M. [UNESP]; Rigueiro, A. L. N. [UNESP]; Soares, C. H. G. [UNESP]; Assumpcao, A. H. P. M. [UNESP]; Dias, E. F. F. [UNESP]; Lirian, K. [UNESP]; Silva, L. A. F. [UNESP]; Millen, D. D. [UNESP]; Chizzotti, M. L. (Wageningen Acad Publ, 2019)
The objective of this study was to evaluate the reduction of adaptation length to high-energy diets to cannulated Nellore cattle using Virginiamycin (VM) as feed additive, in which the following variables were assessed: rumen pH, ox-redox potential, ruminal fermentation end-products, as well as dry matter intake. It was adopted the experimental design in a 5x5 Latin square, where each period lasted 21 days. Five 17 mo-old Nellore yearling bulls were used (415 +/- 22 kg of body weight), and the animals were divided into five treatments: (1) Monensin (MON) (30 mg/kg) and adaptation for 14 days; (2) MON (30 mg/kg) + VM (25 mg/kg) and adaptation for 14 days; (3) VM (25 mg/kg) and adaptation for 14 days; (4) VM (25 mg/kg) and adaptation for 9 days; and (5) VM (25 mg/kg) and adaptation for 6 days. A quadratic effect for adaptation length when only VM was fed was observed for mean pH (P=0.03), duration of pH below 5.2 (P=0.01) and 6.2 (P=0.01), where cattle consuming VM adapted for 9 days had higher mean pH and shorter period of pH below 5.2 and 6.2. Cattle that consumed only MON had lower concentration of butyrate (P=0.02) and higher concentration of propionate (P=0.04) when compared to those consuming VM and adapted for 14 days. It is possible to adapt animals in 14 days consuming only VM as feed additive. However, it is not recommended to shorten the adaptation of these animals to 6 or 9 days.
Keywords: concentrate; fermentation; metabolism